Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Pembelian Produk UMKM Desa (Studi Kasus Pada Konsumen UMKM Keripik Buah UD. Tiga Saudara Desa Tempurejo, Kecamatan Tempursari, Kabupaten Lumajang) - Taufiqurrohman Taufiqurrohman; Agus Widarko; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractIndonesia has many natural resources in abundance. Indonesian people are required to take advantage of existing natural products, by making food or other products and can be a source of community income. With the revolution era that is constantly rolling, all aspects of human needs are assisted by sophisticated technology so that it is easier to sell a product. MSME are examples of businesses that utilize natural products. Armed with quality service and good quality, so that it can create purchasing decisions. Therefore, this study was conducted to determine and analyze the effect of Service Quality and Product Quality on Village MSME Product Purchase Decisions. The case study in this research is MSME UD. Tiga Saudara consumers. The sample in the study used purposive sampling technique and a sample of 100 respondents could be obtained. Methods of data collection using a questionnaire. Multiple linear regression analysis is an analytical technique used in this study. This research shows that there is a simultaneous influence between service quality and product quality which has a significant effect on purchasing decisions. And also partially service quality has a significant effect on purchasing decisions, while product quality has no significant effect on purchasing decisions.Keywords: Purchase Decisions, Service Quality, Produk Quality